Karakteristik Individu, Motivasi dan Kinerja Pelaksana Operasional BUM Desa - Sucahyo Heriningsih; Lita Yulita Fitriyani; Dwi Sudaryati (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
This study aims to determine the effect of individual characteristics and motivation on the performance of BUM Desa operational operators in Bantul Regency. This study uses a survey method that is data collected using a questionnaire. Populations in this study were operational operators of BUM Desa in Bantul Regency as many as 82 people, and the selected sample of 54 people. The sampling method uses a convenience sampling method. The collected data is then analyzed using multiple linear regression analysis methods. The results showed that the work experience and motivation affect the performance of BUM Desa, while gender, education and age did not affect the performance of BUM Desa. This shows that education and age do not guarantee a person's ability to carry out their duties and obligations. The results of this study are expected to be considered by the Village Government in preparing Human Resources to manage the BUM Desa. If BUM Desa is managed by the right Human Resources, has qualified capabilities and appropriate qualifications, then BUMDes can run according to the plans that have been made.